Design of Experiment as a powerful tool when applying Finite Element Method: a case study on prediction of hot rolling process parameters - Giancarlo Giuseppe Bordonaro; Riccardo Leardi; Luca Diviani; Filippo Berto (Fracture and Structural Integrity)
The ultimate goal in hot roll pass design is to manufacture a rolled product with the required dimensional accuracy, defect free surface, and mechanical properties. The proper selection of process parameters is crucial to meet increasing requirements for desired quality and geometrical properties of rolled products. Due to the complex behavior of the metal flow at high temperatures and the severe plastic deformations in shape rolling, most efforts that have been made so far only rely upon the practical experience gained by operators. The large number of variables involved and the difficulty in investigating the process characteristics, make the use of finite element (FE) tools an effective and attractive opportunity towards a thorough understanding of the rolling process.